(untitled) (Journal of Comparative Social Work, 2023)
The last decades have seen a shift towards activation policies in welfare states, such as the introduction programme for refugees in Norway, a qualification programme that seeks to prepare refugees for the labour market. In the last decade, the programme has placed further focus on refugees’ duties rather than their rights, as it had previously done. This article examines the strategies that work counsellors in the introduction programme use to ‘activate’ and assist newly arrived refugees as they prepare to enter the Norwegian labour market. We focus on how work counsellors guide and motivate refugees in this process. We draw on 10 semi-structured interviews with work counsellors in various municipalities in southwestern Norway. We suggest that the activating strategies used by the work counsellors may be seen as a form of aspirations management to get the refugees to shift their aspirations toward those the work counsellors see as more achievable within a shorter period, to get them more quickly into the labour market. We suggest that unchecked power dynamics, together with increasing time-pressure on work counsellors, may be at play leading them to exert too much influence, and leading to user involvement practice not being properly implemented.